STAKEHOLDER ANALYSIS IN POVERTY ALLEVIATION THROUGH THE FAMILY HOPE PROGRAM (PKH) IN SIMOLAWANG VILLAGE, SURABAYA CITY - Ratnasari, Ratnasari (MAP Observer: Jurnal Penelitian Administrasi Publik, 2025)
Poverty is the inability to maintain a minimum standard of living, characterized by limited income to meet basic needs such as clothing, food, and shelter. Low income also makes it difficult to access adequate health care and education, making it difficult to achieve a general standard of living. To address poverty, the Indonesian government has implemented the Family Hope Program (PKH) since 2007. The Family Hope Program (PKH) is a conditional cash assistance program that provides money to extremely poor households. This program aims to improve the lives of poor families and provide access to health and education services. In this study, using stakeholder analysis theory and stakeholder mapping techniques, we can identify stakeholders involved in the implementation of the Family Hope Program (PKH) in Simolawang Village, Surabaya City. There are two categories of stakeholders that need to be considered: those with high influence but low interest, and those with low interest and influence. Stakeholders such as Simolawang Village, Simokerto District, and the Kebonrojo Post Office have significant roles in PKH implementation. However, they have a low level of importance because their primary focus is not specifically on poverty alleviation. Meanwhile, the RW (Neighborhood Unit) Head, RT (Neighborhood Unit) Head, and Great Surabaya Cadres (KSH) have little interest and influence. To improve the effectiveness of PKH, these stakeholders must be actively and strategically involved. Suggestions that can be given include direct mentoring by the Village and Sub-district, emotional and moral support, provision of technical assistance, and strengthening the role of local stakeholders. By collaborating and coordinating between stakeholders, poverty alleviation efforts in Simolawang Village can be more effective and have a significant impact on poor families.